Perceptions of sources of transmission among hospital employees infected with severe acute respiratory coronavirus 2 (SARS-CoV-2) in an urban tertiary care hospital: a qualitative study to inform future pandemic management - Ziyue Luo; Daniel E. Kent; Pooja Shah; Dina Poplausky; MacKenzie Clark MacRae; Cassidy Boomsma; Jacob M. Jasper; Alysse G. Wurcel; Elena Byhoff; Alice M. Tang; Shira Doron; Ramnath Subbaraman (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract